2021
DOI: 10.1055/s-0041-1736567
|View full text |Cite
|
Sign up to set email alerts
|

Disease Progression and Mutation Pattern in a Large Cohort of LGMD R1/LGMD 2A Patients from India

Abstract: Calpainopathy is caused by mutations in the CAPN3. There is only one clinical and genetic study of CAPN3 from India and none from South India. A total of 72 (male[M]:female [F] = 34:38) genetically confirmed probands from 72 independent families are included in this study. Consanguinity was present in 54.2%. The mean age of onset and duration of symptoms are 13.5 ± 6.4 and 6.3 ± 4.7 years, respectively. Positive family history occurred in 23.3%. The predominant initial symptoms were proximal lower limb weaknes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Calpainopathy is typically inherited in an AR manner; however, in recent years, families with a genetic pattern suggesting an AD inheritance have been reported (2)(3)(4)(5)(6). Variants associated with AD calpainopathy include c.643_663del21, c.598_621del15, and the one observed in our patient, c.1333 G>A.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Calpainopathy is typically inherited in an AR manner; however, in recent years, families with a genetic pattern suggesting an AD inheritance have been reported (2)(3)(4)(5)(6). Variants associated with AD calpainopathy include c.643_663del21, c.598_621del15, and the one observed in our patient, c.1333 G>A.…”
Section: Discussionmentioning
confidence: 54%
“…Furthermore, a study conducted in the Netherlands involving patients diagnosed with autosomal recessive LGMD (ARLGMD) through genetic testing revealed that asymptomatic hyperCKemia was present in 6% of all ARLGMD patients and in 3% of calpainopathy patients (7). Case reports from India indicate that 52.1% of calpainopathy patients have limb muscle weakness as their initial symptom, and 20.5% present with toe walking (2). In addition, a high prevalence of ankle contractures and toe walking was observed in a subgroup of patients with an onset age of <12 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The global frequency of LGMD is estimated to be 1one in 14,500-45,000 [ 6 ]. Calpainopathy is prevalent in all autosomal dominant and recessive forms of LGMD, ranging from 40% to 50% in Turkey, Bulgaria, and Indian populations [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…One mutation, CAPN3 c.550delA, is a founder mutation originating from the Eastern Mediterranean and is, with a reported prevalence of 1 in 144,000, the most common mutation of LGMD2A. 1 , 2 , 3 , 4 , 5…”
Section: Introductionmentioning
confidence: 99%